Coatings in Decellularized Vascular Scaffolds for the Establishment of a Functional Endothelium: A Scoping Review of Vascular Graft Refinement - Heng, Jun Wei; Yazid, Muhammad Dain; Abdul Rahman, Mohd Ramzisham; Sulaiman, Nadiah (Frontiers in Cardiovascular Medicine, 2021)
Developments in tissue engineering techniques have allowed for the creation of biocompatible, non-immunogenic alternative vascular grafts through the decellularization of existing tissues. With an ever-growing number of patients requiring life-saving vascular bypass grafting surgeries, the production of functional small diameter decellularized vascular scaffolds has never been more important. However, current implementations of small diameter decellularized vascular grafts face numerous clinical challenges attributed to premature graft failure as a consequence of common failure mechanisms such as acute thrombogenesis and intimal hyperplasia resulting from insufficient endothelial coverage on the graft lumen. This review summarizes some of the surface modifying coating agents currently used to improve the re-endothelialization efficiency and endothelial cell persistence in decellularized vascular scaffolds that could be applied in producing a better patency small diameter vascular graft. A comprehensive search yielding 192 publications was conducted in the PubMed, Scopus, Web of Science, and Ovid electronic databases. Careful screening and removal of unrelated publications and duplicate entries resulted in a total of 16 publications, which were discussed in this review. Selected publications demonstrate that the utilization of surface coating agents can induce endothelial cell adhesion, migration, and proliferation therefore leads to increased re-endothelialization efficiency. Unfortunately, the large variance in methodologies complicates comparison of coating effects between studies. Thus far, coating decellularized tissue gave encouraging results. These developments in re-endothelialization could be incorporated in the fabrication of functional, off-the-shelf alternative small diameter vascular scaffolds.